Mathematics

# Evaluate $\displaystyle \int {\dfrac {(x-1)(x-2)(x-3)}{(x-4)(x-5)(x-6)}}dx$

##### SOLUTION
$I=\displaystyle \int {\dfrac {(x-1)(x-2)(x-3)}{(x-4)(x-5)(x-6)}}dx\\\implies \dfrac {(x-1)(x-2)(x-3)}{(x-4)(x-5)(x-6)}=\dfrac A{x-4}+\dfrac B{x-5}+\dfrac C{x-6}\\\implies (x-1)(x-2)(x-3)=A(x-5)(x-6)+B(x-4)(x-6)+C(x-4)(x-5)$Put $x=5$$4\times3\times2=B(1)(-1)\\\implies B=-24Put x=6$$5\times 4\times 3=C(2)(1)\\\implies C=30$Put $x=4$$3\times 2\times 1=A(-1)(-2)\\\implies A=3$Therefore, $I=\int {\left(\dfrac 3{x-4}-\dfrac {24}{x-5}+\dfrac {30}{x-6}\right)}dx\\\implies I=3\ln{|x-4|}-24\ln{|x-5|}+30\ln{|x-6|}+C$

Its FREE, you're just one step away

Subjective Medium Published on 17th 09, 2020
Questions 203525
Subjects 9
Chapters 126
Enrolled Students 114

#### Realted Questions

Q1 Subjective Medium
$\text { Evaluate: } \displaystyle \int \dfrac{e^{x}}{\sqrt{5-4 e^{x}-e^{2 x}}} \mathrm{d} \mathrm{x}$

1 Verified Answer | Published on 17th 09, 2020

Q2 Single Correct Medium
Let $\displaystyle f\left ( x \right )=\frac{\sin x}{x},then\:\int_{0}^{\pi /2}f\left ( x \right )f\left ( \frac{\pi }{2}-x \right )dx=$
• A. $\displaystyle \int_{0}^{\pi }f\left ( x \right )dx$
• B. $\displaystyle \pi \int_{0}^{\pi }f\left ( x \right )dx$
• C. $\displaystyle \frac{1}{\pi } \int_{0}^{\pi }f\left ( x \right )dx$
• D. $\displaystyle \frac{2}{\pi }\int_{0}^{\pi }f\left ( x \right )dx$

1 Verified Answer | Published on 17th 09, 2020

Q3 Subjective Medium
Evaluate  $\displaystyle \int_{a}^{b} \dfrac{1}{\sqrt{(x-a)(b-x)}}dx,b>a$

1 Verified Answer | Published on 17th 09, 2020

Q4 Single Correct Hard
$\int { { ({ x }^{ 2 }+5) }^{ 3 } } dx$
• A. $\cfrac { { x }^{ 6 } }{ 7 } +3{ x }^{ 5 }+25{ x }^{ 3 }+125x+C$
• B. $\cfrac { { x }^{ 7 } }{ 7 } +3{ x }^{ 5 }-25{ x }^{ 3 }+125x+C$
• C. $\cfrac { { x }^{ 7 } }{ 7 } +4{ x }^{ 5 }+25{ x }^{ 3 }+125x+C$
• D. $\cfrac { { x }^{ 7 } }{ 7 } +3{ x }^{ 5 }+25{ x }^{ 3 }+125x+C$

$\int \dfrac{1+x}{\sqrt{1-{x}^{2}}}$dx